(untitled) (مجلة جامعة سرت للعلوم الانسانية, 2023)
The city of Ghat is one of the most important centers of human settlement in the Sahara throughout history, due to its location of great importance as a transit point between the east, west, north and south of the desert. The modern, topographic diversity was an important factor in the city’s preservation of its features that were drawn by long decades of originality and the preservation of the cultural heritage through time. Ghat, like other cities in the south, needs development and development as a settlement center that can expand to attract larger numbers of residents, especially as it is a place that possesses natural and human ingredients and has the appropriate conditions for that. Question that (what are the geographical controls that affect the sustainable spatial development in the city of Ghat) , The answer to this question aims to identify the repercussions of geographical conditions on the spatial development programs in the city of Ghat, and to know the extent of their sustainability in the presence of these conditions. Ghat from others, in an attempt to reach results through which to draw a future picture of sustainable spatial development in the southwest of Libya, whose capital and urban and settlement center is the city of Ghat. Through these results, recommendations can be formulated that help lay the foundations for sustainable development in this region.